Sanger sequencing reveals Pseudomonas aeruginosa was the most common cross-contamination of gastrointestinal endoscopy - Zainab hameed (Wasit Journal for Pure Sciences)
A common cause of nosocomial infections is Pseudomonas aeruginosa. Has become a significant pathogen over the last two decades, accounting for 10% to 20% of infections in many hospitals. It demonstrates an inherent resistance to numerous antibiotics. This study was aimed to utilized advanced molecular techniques to identified Pseudomonas spp. that caused cross-contamination of stomach biopsies specimens taken by gastrointestinal endoscopy and its resistance to some common used antibiotics.